DEVELOPING A LOCAL INSTRUCTION THEORY FOR LEARNING COMBINATIONS - Ika Meika; Didi Suryadi; Darhim Darhim (IKIP Siliwangi and I-MES, 2019)
This research aims at developing local instruction theory for learning combinations by using Realistic Mathematics Education (RME). This research uses a design research approach, Hypothetical Learning Trajectory (HLT), developed from a series of activities to obtain a better understanding about combinations at Senior High School (SHS) students. Theoretical development is supported by an interactive process in designing learning activities, conducting teaching experiment and conducting retrospective analysis to contribute to combinations of Local Instruction Theory (LIT). An understanding of combinations emerges and develops during classroom learning activities. Qualitative analysis of teaching experiments shows that by using local instruction theory teaching materials that characterize RME students are able to develop their understanding about a combination.